Lobbying from Inside the System: Why Local Governments Pay for Representation in the U.S. Congress. (March 2015) - Loftis, Matt W.; Kettler, Jaclyn J.
Why do cities spend scarce resources lobbying the federal government? The hierarchy of U.S. government provides various pathways for local representation. Nevertheless, cities regularly invest in paid representation. This presents a puzzle for American democracy. Why do cities lobby, and do they lobby strategically? We quantify for the first time the extent of this phenomenon and examine its determinants using new data on 498 cities across forty-five states from 1998 to 2008. We find that economic distress pushes cities to lobby, but does not impact expenditures. Cities in competitive congressional districts, and therefore crucial to national politics, spend more on lobbying.